Web interactive multimedia technology implementation: a university context - Md Ali, Asma; Richardson, Joan (2012)
Elluminate a web interactive multimedia technology (WIMT), was introduced in a large metropolitan university. The system incorporates several interactive and multimedia features. Those features when used in teaching and learning activities are categorised into five affordances: text, audio, video, image and screen-board. This system provides real time collaboration when used in a university teaching and learning environment as it enables immediate feedback between participants across physical space. This provides opportunities for interactivity and relationship building between academics and students, a vital component of learning. However, there are also several constraints in using WIMT. This paper discusses the findings from a case study conducted using a design science research approach. Semistructured interviews were employed to gather the implementer’s and adopter’s perspective on their use of WIMT. The findings demonstrate the benefits and challenges in using WIMT for teaching and learning activities. The practical description of experienced implementer and adopter can be used as a guide for others.